2008
DOI: 10.1097/wnr.0b013e3282ff6396
|View full text |Cite
|
Sign up to set email alerts
|

CD133+ cells from human peripheral blood promote corticospinal axon regeneration

Abstract: To assess the effect of endothelial progenitor cells on the axon growth of cortex neurons, we transplanted CD133 cells derived from human peripheral blood to an organotypic coculture system consisting of spinal cord and cortex from neonatal rats. The axon growth from cortex to spinal cord was significantly promoted in cultures after CD133 cells transplantation compared with that of the control cultures. In addition, real-time reverse transcription-PCR showed a significant upregulation of vascular endothelial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…13,14 The CD133 + cells were labeled with a magnetic bead, and isolated from human peripheral blood using a magnetic cell separation instrument. 15 We hypothesized that immunomagnetic CD133…”
mentioning
confidence: 99%
“…13,14 The CD133 + cells were labeled with a magnetic bead, and isolated from human peripheral blood using a magnetic cell separation instrument. 15 We hypothesized that immunomagnetic CD133…”
mentioning
confidence: 99%
“…Life expectancies range from 15 to 47 months after presentation [8,6] even after Riluzole treatment. Stem cell transplantation is a potential therapeutic strategy for ALS patients, as well as for other neurodegenerative disorders [41,43,44,45,[34][35][36][37][38]22] that CD133+ stem cells isolated from the peripheral blood can differentiate into neurons [27,28,31].…”
Section: Discussionmentioning
confidence: 99%
“…These cells can be easily isolated from the peripheral blood or bone marrow (BM) [25][26][27][28][29][30]. It has been demonstrated that stem cells isolated from peripheral blood of ALS patients, can be induced to differentiate into preneurons or stem cells isolated from human BM are capable to differentiate into neurons [31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations